Putting Community Based Tourism into Practice: The Case of the Cree Village Ecolodge in Moose Factory,Ontario - Graci, Sonya (Téoros)

(untitled) (Université du Québec à Montréal, 2012)
To move towards sustainability, tourism must contribute to the empowerment of local communities. This can be achieved through community participation in decision-making where essential information is gained, with the early stages of empowerment allowing the community to determine their own development (Cole, 2006). Community capacity building ensures the benefit of tourism to the local community by developing skills and entrepreneurial spirit to become part of the tourism industry, which will lead to the reduction of negative impacts. This article focuses on the community of Moose Factory that used a community based approach to create one of the world’s top ecolodges. It was collaboratively developed in an attempt to provide economic, social and cultural livelihoods. Strategies used to develop and involve the community will be discussed.